2016
DOI: 10.1080/03019233.2016.1219542
|View full text |Cite
|
Sign up to set email alerts
|

A study of pre-briquetting granulation sintering of the mixtures with high ratio of Brazilian specularite concentrate

Abstract: In the paper, the pre-treatment of fine Brazilian specularite concentrates with high iron grade and low impurities through pre-briquetting was proposed to improve the granulation and sintering performance of blends comprising some 30% specularite concentrates. The results show that the excellent sintering indexes are attained as follows in pot tests: productivity of 1.64 t m −2 h −1 , tumble index of 59.87% and solid fuel consumption of 71.64 kg t −1 under the optimal conditions. Compared with traditional sint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…[ 16 ] For the CBB with 7% and 10% sodium silicate, the RDI +3.15 is more than 60%, which meets the requirements of blast furnace;; however, the value of RDI −0.5 is too high to meet the requirements. [ 27 ] It can be seen from Figure 4d, CBB of starch and bentonite have no strength after the RDI test, while the CBB strength of sodium silicate is more than 160 N. It is illustrated that sodium silicate can consolidate sinter particle at 500 °C and improve the thermal strength of CBB. Sodium silicate separates out the silica acid gel after dewatering and hardening at high temperature.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…[ 16 ] For the CBB with 7% and 10% sodium silicate, the RDI +3.15 is more than 60%, which meets the requirements of blast furnace;; however, the value of RDI −0.5 is too high to meet the requirements. [ 27 ] It can be seen from Figure 4d, CBB of starch and bentonite have no strength after the RDI test, while the CBB strength of sodium silicate is more than 160 N. It is illustrated that sodium silicate can consolidate sinter particle at 500 °C and improve the thermal strength of CBB. Sodium silicate separates out the silica acid gel after dewatering and hardening at high temperature.…”
Section: Resultsmentioning
confidence: 96%
“…[ 26 ] Figure 4c shows the RDI value of CBB, and the RDI +3.15 value of starch and bentonite is below 60% which can't meet the requirements of blast furnace. [ 27 ] According to our previous research, the starch decomposes at about 340 °C. [ 15 ] Therefore, the strength of CBB decreases sharply when the temperature exceeds 340 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Several works have been developed trying to attenuate the impact of the fines on the sintering bed permeability. These include new routes of cold agglomeration, optimization of water [15], binder additions [16], and pre-briquetting [17]. Recently, some authors [18,19] have also suggested decreasing particle size of adherents as an alternative to improve granulation performance.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the poor granulation behaviour of iron concentrates, its usages in the traditional sintering process are greatly limited. Meanwhile, in order to improve the quality of the agglomeration products, some methods such as increasing the proportion of limes in sintering mixture and pre-treating iron concentrates through mechanical activation should be proposed to improve the iron concentrates granulation [4][5][6][7]. However, the presence of unreacted limes has a negative effect on metallurgical properties (especially disintegration during reduction) as well as on strength.…”
Section: Introductionmentioning
confidence: 99%